2013
DOI: 10.1159/000355088
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Temperature in Asthmatics and Controls after Eucapnic Voluntary Hyperventilation and a Methacholine Challenge Test

Abstract: Background: It has been suggested that exhaled breath temperature (EBT) is increased in asthmatic subjects. Objectives: Our aim was to investigate EBT in asthmatics compared to healthy controls before and after eucapnic voluntary hyperventilation (EVH) and a methacholine challenge test (MCT). Methods: A total of 26 asthmatics and 29 healthy controls were included. Forced expiratory volume in 1 s (FEV1), EBT and oral, axillary and auricular temperatures were measured before and after EVH and MCT. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Peroni et al [21] found no correlation with EBTp in 50 children with asthma treated with ICS after exercise-induced bronchoconstriction, while in asthmatic children not treated with ICS they found an increase in EBTp and a decrease in FEV 1 after the same exercise. Svensson et al [22] did not find changes in EBTp in asthma patients before or after two bronchoconstriction tests (eucapnic voluntary hyperventilation and methacholine challenge). These differences between studies could be explained by the anti-inflammatory effect of ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Peroni et al [21] found no correlation with EBTp in 50 children with asthma treated with ICS after exercise-induced bronchoconstriction, while in asthmatic children not treated with ICS they found an increase in EBTp and a decrease in FEV 1 after the same exercise. Svensson et al [22] did not find changes in EBTp in asthma patients before or after two bronchoconstriction tests (eucapnic voluntary hyperventilation and methacholine challenge). These differences between studies could be explained by the anti-inflammatory effect of ICS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that bronchial inflammatory processes may cause vascular dilation and increase bronchial blood flow, which may be responsible for the increase in exhaled breath temperature in asthma patients [88,89]. …”
Section: Studies Conducted On Exhaled Airmentioning
confidence: 99%
“…Recently, Svensson et al [88,90] showed that exhaled breath temperature increases after exercise as well as after both eucapnic voluntary hyperventilation and methacholine challenge tests. In all cases, this is related to the fall in both FEV 1 and the oral temperature, suggesting a vascular response.…”
Section: Studies Conducted On Exhaled Airmentioning
confidence: 99%
“…Histopathological and morphometric observations confirmed this result showing an increase of the smooth muscle layer thickness and accumulation of mucus leading to the obstruction of the bronchial lumen. Previous studies indicated that MeCh effect on bronchial smooth muscle cells, endothelial cells and mucus-producing cells was mediated by muscarinic receptors with an increase in intracellular calcium (Van Schoor, Joos, Pauwels, 2000;Anderson, 2010;Svensson, Bjermer, Tufvesson, 2014). Interestingly, we showed for the first time that PACAP analog as well as PACAP38 and Terb potentially reversed airway resistance induced by MeCh.…”
Section: Discussionmentioning
confidence: 53%